2015
DOI: 10.1093/cid/civ202
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of Mortality in Patients With Ebola Virus Disease

Abstract: In an observational cohort study including 89 Ebola patients, predictive factors of death were analyzed. The crude mortality rate was 43.8%. Myalgia (adjusted odds ratio [OR], 4.04; P = .02), hemorrrhage (adjusted OR, 3.5; P = .02), and difficulty breathing (adjusted OR, 5.75; P = .01) were independently associated with death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 14 publications
2
19
1
Order By: Relevance
“…2-5 All 5 patients who died were 42 years of age or older; in various studies, age older than 40 years or older than 45 years has been identified as a risk factor in West Africa. 2,21,22 The percentage of patients who died could have been as high as 41% (11 of 27 patients), with up to six additional deaths, if advanced organ support had been unavailable for 2 survivors who received noninvasive ventilation, 2 survivors who received invasive mechanical ventilation, and 2 survivors who received both invasive mechanical ventilation and continuous renal-replacement therapy. A key feature of the clinical care of patients with EVD who were treated in Europe and the United States was the availability of laboratory testing to closely monitor electrolyte levels and hematologic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2-5 All 5 patients who died were 42 years of age or older; in various studies, age older than 40 years or older than 45 years has been identified as a risk factor in West Africa. 2,21,22 The percentage of patients who died could have been as high as 41% (11 of 27 patients), with up to six additional deaths, if advanced organ support had been unavailable for 2 survivors who received noninvasive ventilation, 2 survivors who received invasive mechanical ventilation, and 2 survivors who received both invasive mechanical ventilation and continuous renal-replacement therapy. A key feature of the clinical care of patients with EVD who were treated in Europe and the United States was the availability of laboratory testing to closely monitor electrolyte levels and hematologic status.…”
Section: Discussionmentioning
confidence: 99%
“…21 Difficulty breathing at admission was associated with a fatal outcome among patients with EVD in Guinea. 22 Overall, 9 of the patients with EVD (33%) who were cared for in the United States or Europe received noninvasive ventilation or invasive mechanical ventilation for respiratory failure. The 2 patients with EVD who received noninvasive ventilation alone survived; however, of the 7 patients who received invasive mechanical ventilation, the 3 patients who also had renal failure that required continuous renal-replacement therapy died.…”
Section: Discussionmentioning
confidence: 99%
“…The recent epidemic of Ebola Virus in West Africa has highlighted this difficulty [3,4]. The lack of mechanism for the management of hemorrhagic diseases could explain the high lethality associated to this epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of mechanism for the management of hemorrhagic diseases could explain the high lethality associated to this epidemic. Indeed, the presence of hemorrhage is considered as a pejorative prognostic factor in a patient with Ebola Virus disease [4].…”
Section: Introductionmentioning
confidence: 99%
“…As of September 16, 2015, the World Health Organization reported 28,220 confirmed, probable, and suspected EVD cases and 11,291 deaths in Guinea, Liberia, and Sierra Leone4. EVD is an infectious disease characterized by high fatality and rapid progress to an outcome of death or recovery, with a fatality rate of 50–90%567. For the ongoing outbreak, the fatality rate for confirmed cases (15,199) is 74.3%.…”
mentioning
confidence: 99%